Haematological characteristics of individuals from nine species of Australian cockatoos in response to naturally occurring disease and injury - Clark, Phillip; Boardman, W.S.J.; Raidal, S.R. (Springer U K, 2013)
Birds, both captive and free living, may encounter health challenges and haematological assessment provides important insight into the response to these challenges. We investigated the haematological characteristics, in response to a range of injuries and naturally occurring disease, exhibited by 31 birds from nine species of Australian cockatoos. The birds exhibited packed cell volume between 0.14 and 0.55 l/l with a maximum proportion of 12.5 % polychromatophilic erythrocytes. A spectrum of leukocyte responses was observed. The total leukocyte concentration was between 2.20 and 50.00×109/l. The heterophil concentration was between 0.86 and 47.25×109/l and the lymphocyte concentration was between 0.27 and 16.47×109/l. Morphological atypia of leukocytes was evident for 27/31 (87.1 %) birds. This study illustrates the heterogeneous haematological response exhibited by Australian cockatoos.